Dental caries and developmental defects of enamel in relation to fluoride levels in drinking water in an arid area of Sri Lanka - Ekanayake, L.; Hoek, Wim van der (Karger AG, 2002)
The study was conducted to assess caries and developmental defects of enamel in relation to fluoride levels in drinking water and the association between caries experience and the severity of diffuse opacities in children living in Uda Walawe, an area with varying concentrations of fluoride in drinking water in Sri Lanka. A total of 518 14-year-old children who were lifelong residents in this area were examined for dental caries and developmental defects of enamel. But the present analysis is confined to 486 children from whom drinking water samples were collected. The prevalence of enamel defects and diffuse opacities ranged from 27 to 57% while the prevalence of caries ranged from 18 to 29% in the different fluoride exposure groups. The prevalence of enamel defects increased significantly with the increase in the fluoride level in drinking water. Both the caries prevalence and the mean caries experience were significantly higher in children with diffuse opacities than in those without in the group consuming water containing >0.70 mg/l of fluoride. The association between dental caries and the severity of diffuse opacities was also significant only in this group. Children with the mildest form of opacities (DDE scores 3 and 4) had the lowest DMFS (0.25 +/- 0.7), and the highest DMFS (1.1 +/- 1.7) was found in those with the most severe form of opacities (DDE score 6). In conclusion, the relationship that was observed in this study between fluoride levels in drinking water, diffuse opacities and caries suggests that the appropriate level of fluoride in drinking water for arid areas of Sri Lanka is around 0.3 mg/l. Also individuals with severe forms of enamel defects in high-fluoride areas are susceptible to dental caries.